The Governance Policy for Strengthening Democracy in Papua - Batilmurik, Ridolof (Department of State Administration - Musamus University, 2024)
This article explores governance policies aimed at strengthening democracy in Papua, a region with unique social, cultural, and political characteristics. The study begins by addressing the challenges Papua faces in the democratic development process, particularly in relation to governance structures and the role of local communities. Special Autonomy and decentralization policies have offered opportunities, but significant obstacles remain in achieving inclusive and participatory democracy. The focus is on examining the effectiveness of governance policies implemented in Papua, specifically in relation to democratic consolidation and the engagement of indigenous communities in decision-making processes. The primary goal of this research is to evaluate how governance policies contribute to the promotion of a more robust, participatory democracy in Papua, while identifying areas where policy adjustments are needed. Methodology: Using qualitative methods, the study involves an in-depth analysis of policy documents, interviews with local stakeholders, and a review of relevant literature. A comparative approach is also employed to assess the impact of governance reforms on democracy in Papua relative to other regions in Indonesia. The findings reveal that while governance policies have led to improvements in local democratic practices, gaps remain in terms of inclusivity and accountability. Key issues include limited representation of indigenous populations and challenges in the implementation of decentralization. The article concludes that further refinement of governance policies is necessary to strengthen democracy in Papua. Policy reforms should prioritize greater inclusion of local communities, enhanced transparency, and increased capacity-building for local governance institutions.